2018
DOI: 10.3390/s18061925
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Position-Determination Approach for Multiple Sources Based on Neural Network Computation

Abstract: The most widely used localization technology is the two-step method that localizes transmitters by measuring one or more specified positioning parameters. Direct position determination (DPD) is a promising technique that directly localizes transmitters from sensor outputs and can offer superior localization performance. However, existing DPD algorithms such as maximum likelihood (ML)-based and multiple signal classification (MUSIC)-based estimations are computationally expensive, making it difficult to satisfy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…For superiorities of parallelism and easy implementation by hardware, the RNN model can be implemented by utilizing embedded systems such as field-programmable gate arrays (FPGAs) [26,27,60]. Many state-of-the-art studies [27,61,62] have been reported for the effective implementation of the neural network model such as the MLP. In [27], the MLP was effectively implemented by utilizing the FPGA Ciclone IV GX FPGA DE2i-150 from Altera.…”
Section: Preliminaries and Neurodynamic Approachesmentioning
confidence: 99%
“…For superiorities of parallelism and easy implementation by hardware, the RNN model can be implemented by utilizing embedded systems such as field-programmable gate arrays (FPGAs) [26,27,60]. Many state-of-the-art studies [27,61,62] have been reported for the effective implementation of the neural network model such as the MLP. In [27], the MLP was effectively implemented by utilizing the FPGA Ciclone IV GX FPGA DE2i-150 from Altera.…”
Section: Preliminaries and Neurodynamic Approachesmentioning
confidence: 99%
“…1,[10][11][12] Artificial neural networks (ANNs) [13][14][15][16] represent an another direction of research for solving the DoA problems in real-time. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Beside ANNs, the more general methods in the field of artificial intelligence, such as genetic programming (GP) and support-vector machines (SVM), are used in today research for the same purpose, as demonstrated for the DoA estimation problem solving in Reference 35 and Reference 36, respectively. Although the GP and SVM-based DoA models have more generalization capabilities than the ANN models in modeling highlynonlinear dependences present in DoA problems, DoA ANN models still represent a good alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researches have been focused to adapt some of the previously mentioned super‐resolution algorithms, based on time‐consuming inverse matrix calculations and Eigen‐value decompositions, to the strict real‐time demands . Artificial neural networks (ANNs) represent an another direction of research for solving the DoA problems in real‐time . Beside ANNs, the more general methods in the field of artificial intelligence, such as genetic programming (GP) and support‐vector machines (SVM), are used in today research for the same purpose, as demonstrated for the DoA estimation problem solving in Reference and Reference , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the ENN can be regarded as an especial kind of feed-forward NN with added memory neurons. The ENN has certain dynamic fits over the static neural network (NN) [ 17 , 18 , 19 ], owing to the context nodes in the ENN. In addition, the ENN has been applied abroad for identification and control of systems [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%